(untitled) (المجلة العربية للعلوم و نشر الأبحاث, 2021)
Research in the letters of meanings to be mentioned; In order to fulfill the meaning for which it was set, but as a matter of the breadth that the Arabic language enjoys, the letters of meanings are characterized by deletion, degeneration, embedding or increase, but this behavior is not without justification or evidence, and this is what this research will deal with taken from the book “poetry” by Abu Ali Al-Farsi is a model... as Al-Farsi deals with this phenomenon in some detail in his book the aforementioned, and this research will follow him, monitoring his treatment of these phenomena that affect the letters of meanings, through his treatment of evidence from the words of the Arabs in their poetry. The research concludes with results that reveal that Abu Ali followed the mass of grammarians, or his uniqueness with opinions that he had not previously met, when he studied this phenomenon.